The problem of search safe and effective method in reducing injuries in bodybuilding stage of specialized basic training - O.S. Slavityak (Physical Education of Students)
Purpose: To identify the most frequently used coaches and athletes in bodybuilding principles that can help to reduce the injuries of athletes while maintaining the progressivity results. Material : a survey participated 86 coaches and 120 athletes, bodybuilders from 5 to 8 years. Results : It was found that most of the coaches used in the course of employment principles generally accepted system of training. In such circumstances, the risk of injury to athletes is large enough. When using pre-exhaustion principle to increase the intensity of the training process increases the risk of overloading the body athletes. Conclusions : Athletes with a longer training experience (about 8 years), more likely to use the principle of prior exhaustion. In this case athletes try using this principle to reduce the operating parameters of volume load. This helps to reduce the level of injury and maintain positive dynamics performance.